A Humanistic Approach of Public Services Implementation as an Effort to Achieve Good Governance - Hendrawan Prasetyo (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to find out how public services are by using a humanistic approach organized by public service agencies as an effort to realize good governance. The public service agency under study was the Population and Civil Registry Office of Kebumen Regency. What is meant by the humanistic approach in the administration of public services in this research is the approach used in public services by prioritizing humanist/human values. This study uses a qualitative approach, which seeks to obtain as complete information as possible about public services carried out by the public service actors in the Population and Civil Registry Office of Kebumen Regency, which was explored through observation, documentation, and in-depth interviews with informants consisting of employees of the Population Service and Kebumen District Civil Registry and the public service users in the Population and Civil Registration Office of Kebumen Regency. In this study, writing is focused on issues relating to the delivery of public services using a humanistic approach for the realization of good governance. The humanistic approach in public services involves three aspects in the delivery of public services, namely the role of human resources shown through the attitude of the public service apparatus in serving the community, the process/mechanism/procedure of services carried out in the administration of public services, as well as facilities and infrastructure that support public services. Respect for humans is reflected in how the public service apparatus behaves towards the community they serve. The demand for good behavior which includes friendly, smiling, patient, empathy, and sympathy is an absolute thing in the Kebumen Regency's Population and Civil Registry Office in serving the community. Public services with a humanistic approach prioritize reciprocal communication between the public service apparatus and the people served.Keywords: good governance, humane, humanistic approach, public service.